Transport policy in Belgium: Translating sustainability discourses into unsustainable outcomes. (January 2017) - Boussauw, Kobe; Vanoutrive, Thomas
Abstract: In this paper, we challenge the so-called orthodox sustainable transport vision, by confronting it with two possibly troublesome issues; (1) the urge for growth, and (2) the question of social justice. On the basis of seven cases from Belgium, a country with a strong commuting culture and a traditional tendency towards multimodality, we show that the conversion of a sustainability discourse into policy actions often leads to realisations which are essentially to be labelled as non-sustainable. On the one hand we discuss a number of cases where additional travel is unintentionally stimulated, with an unforeseen contribution to global warming as a result. On the other hand, we refer to cases where subsidies for sustainable transport modes seem to be geared towards wealthier groups, while poorer groups are exposed to additional expenses. The cases cover different steps of the policy process: (1) problem definition and selection of indicators, (2) the choice of a particular solution, and (3) the design of the chosen plan or programme, and illustrate the mechanisms underlying goal-displacements. Highlights: In Belgium, there is a gap between sustainable transport discourse and policy. The unabated urge for growth and the question of social justice are disregarded. Problem definition, choice of solutions, and bureaucracy explain the observed gap.